2018
DOI: 10.1080/17483107.2018.1470685
|View full text |Cite
|
Sign up to set email alerts
|

Low vision and mobility scooters: the experiences of individuals with low vision who use mobility scooters

Abstract: Four themes were found to describe experiences: autonomy and well-being, accessibility, community interactions and self-regulation. Discussion and implications: This study was a pilot for a larger study examining self-regulation in scooter users. However, as roles emerge for health professionals and scooters, the findings also provide evidence to inform practice, because it demonstrates the complex meaning and influences on performance involved in low vision mobility scooter use. Implications for rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Participants were also asked to provide a recent optometry or ophthalmology report to describe each participant’s level of visual impairment. Based on experience from a previous study (McMullan and Butler, 2018), it was assumed participants would have optometry/ophthalmology reports available, eliminating the need to make further vision measurements. Unfortunately, it was found that the vision reports provided inconsistent information, most including only visual acuity and visual field, but not contrast sensitivity, glare sensitivity, useful field of view or any comparative measures of functional vision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were also asked to provide a recent optometry or ophthalmology report to describe each participant’s level of visual impairment. Based on experience from a previous study (McMullan and Butler, 2018), it was assumed participants would have optometry/ophthalmology reports available, eliminating the need to make further vision measurements. Unfortunately, it was found that the vision reports provided inconsistent information, most including only visual acuity and visual field, but not contrast sensitivity, glare sensitivity, useful field of view or any comparative measures of functional vision.…”
Section: Methodsmentioning
confidence: 99%
“…Peer-reflexivity was enhanced through presentations to and discussion with occupational therapists and other stakeholders (Shenton, 2004). Both this study and the previous study (McMullan and Butler, 2018) were introduced in online presentations, at visual impairment consumer group meetings and at conferences, welcoming scrutiny from peers including practising NZ occupational therapists and others interested in visual impairment, accessibility and disability rights. The use of participant observation (the go-along) and interview provided a form of triangulation with all but the three participants who declined the go-along (Shenton, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies point to the trade-offs when using powered wheelchairs and scooters in terms of their ability to traverse longer distances versus challenges when maneuvering in confined spaces including compromised safety (e.g., higher rates of collisions causing personal injury, device damage, and injury to people nearby) [67,73,80,81]. Comorbidities such as vision and cognitive impairments could further impede safety and performance in device maneuvering tasks [82,83]. Wheelchair skills training for potential transit users would need to emphasize proficiency in tasks related to transit use, such as 180 • turns and parallel park maneuvers within constrained spaces and/or in close proximity to other people, and negotiating ascent-descent while turning on to narrow access ramps [84,85].…”
Section: Implications For Rehabilitationmentioning
confidence: 99%